Tursiocola denysii sp. nov. (Bacillariophyta) from the neck skin of Loggerhead sea turtles (Caretta caretta) - Frankovich, Thomas Anthony; Sullivan, Michael J.; Stacy, Nicole Indra (Phytotaxa, 2015)
Tursiocola denysii sp. nov. is described from the dorsal neck skin of loggerhead sea turtles (Caretta caretta), bringing the total number of known species in the genus Tursiocola to eight. A gradient of striae density on the valve face, the low length:width ratio of the valves, radiate striae at mid-valve, and a second partial row of pores on the valvocopulae are characteristics that expand the range of morphological diversity within the genus. The different morphology of the pars interior and the pars exterior of the valvocopula is described for the first time in the genus. T. denysii accounted for up to ca. 40% of all diatom valves on the skin of loggerhead turtles. This is the first report of a new epizoic diatom species from the skin of loggerhead sea turtles.